1999
DOI: 10.1136/hrt.81.4.352
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life four years after acute myocardial infarction: short form 36 scores compared with a normal population

Abstract: Objectives-To assess the impact of myocardial infarction on quality of life in four year survivors compared to data from "community norms", and to determine factors associated with a poor quality of life. Design-Cohort study based on the Nottingham heart attack register. Setting-Two district general hospitals serving a defined urban/rural population. Subjects-All patients admitted with acute myocardial infarction during 1992 and alive at a median of four years. Main outcome measures-Short form 36 (SF 36) domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
132
2
14

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(168 citation statements)
references
References 19 publications
15
132
2
14
Order By: Relevance
“…Acute Myocardial Infarction has negative consequences on the health related quality of life of the patients and that leads to lowering of their health related quality of life even several years after the acute myocardial infarction. During the first month after the acute myocardial infarction patients are very vulnerable physically, mentally and emotionally [5]. It has been found that patients after MI reported the impairment in their daily lives, such as household work, physical activities and hobbies.…”
Section: Adaptability Is Not Imitation Means Power Of Resistance and mentioning
confidence: 99%
See 1 more Smart Citation
“…Acute Myocardial Infarction has negative consequences on the health related quality of life of the patients and that leads to lowering of their health related quality of life even several years after the acute myocardial infarction. During the first month after the acute myocardial infarction patients are very vulnerable physically, mentally and emotionally [5]. It has been found that patients after MI reported the impairment in their daily lives, such as household work, physical activities and hobbies.…”
Section: Adaptability Is Not Imitation Means Power Of Resistance and mentioning
confidence: 99%
“…A study had found that patients after MI had reported the impairment in their daily life, such as household work, physical activities such as climbing stairs, sexual activities and hobbies, unable to perform the same level of work that they could do before the diagnosis of disease and low mood. Thus, physical and emotional disturbance of an acute MI can have permanent and in many cases, damaging effects on the life styles at post MI, thereby decreasing overall QOL for long run [5]. After coming across the studies related to myocardial infarction and quality of life, interest aroused in the investigator to her investigate and find out the quality of life among post myocardial infarction patients and its association with socio-demographic variables respectively.…”
Section: Need For Studymentioning
confidence: 99%
“…At the present time, the Medical Outcomes Study 36-item Short-Form Health Survey (SF-36) used in this project is the most valid instrument for measuring the quality of life of patients with coronary disease and its use has been proven in the clinical forms of both angina and myocardial infarction (Failde & Ramos, 2000). Likewise, it is an appropriate tool for use in patients who undergo heart surgery and as an evaluative measure in intervention programmes (Brown et al, 1999;Dougherty et al, 1998;Hawkes & Mortensen, 2006;Yu et al, 2003).…”
Section: Assessing Quality Of Life In Coronary Patientsmentioning
confidence: 99%
“…The HRQoL is defined as "individuals' perception of their position in life in the context of the culture and value systems in which they live, and in relation to their goals, expectations, standards and concerns", according to the World Health Organization [32]. The HRQoL following acute MI is affected by emotional distress, angina pectoris, side effects induced by drug therapy and comorbidities [33]. A study of 198 patients who underwent elective catheterization [34] found that depression and anxiety independently predicted diminished self-reported physical function and activity interference at 6-and 12-month follow-up.…”
Section: Discussionmentioning
confidence: 99%